Exploring China’s digital public diplomacy in Africa in the time of Pandemic: Building a China-Africa global community of health for all? - (:unkn) unknown (My University, 2022)
The study aimed to advance academic understanding of the Chinese government’s use of social media in the public diplomacy arena. In other words, we explored how Beijing’s (para-)diplomats mobilized Twitter to defend the government’s political interests during the COVID-19 pandemic. In particular, we focus on China’s digital public diplomacy strategy vis-à-vis African countries regarding COVID-19 management and vaccines under the political blueprint of a China-Africa community with a shared future. We assume that Beijing has used Twitter to create its self-centered network of actors to spread the selective facts it defends. Specifically, we will identify the most influential Chinese public diplomacy Twitter accounts and their online interactions with other counterparts and partners in terms of users and interactions. In terms of content, we will determine Beijing’s thematic narratives for China-Africa cooperation in fighting the pandemic to interpret China’s current narrative and rhetoric strategies. To this end, we propose three research questions: 1) How do Chinese public diplomacy actors in Africa use Twitter to build an online engagement network, and what are the characteristics of this actor network? 2) What is Beijing’s online communication phases on “China-Africa” anti-pandemic collaboration issues from May 2020 to November 2021? 3) What are the narrative strategies of Chinese public diplomacy actors regarding “China-Africa” anti-pandemic collaboration in favor of building a China-Africa Community of Health for all?
Keywords: African Research